Dendrochronological method of assessment of forestry measures effect on the growth fluctuation of common oak in old-growth stands - Kopiy, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2024)
There have been analysed theoretical aspects of using dendrochronological methods to study the effect of forestry measures on the growth and development of woody plants. The dendrological methods make it possible to assess a relative effect of various factors, both natural and anthropogenic, on the development including forest stands as well. These can be used to study the spatiotemporal dynamics of forest ecosystems. The information provided is of particular importance for solving global, regional and local problems resulting from human impact on the ecosystems. The most promising vein of forestry research using dendrochronology is the study of chronological spatio-temporal dynamics of forest ecosystems effected by natural and anthropogenic factors. The effectiveness of various forestry measures taken can be successfully evaluated. Recording the annual increase in the rate of stands growth in the region investigated is a sort chronicle of the stands growth and development. The article presents statistical data on distribution and dynamic changes of oak growing areas in Ukraine. Emphasis is placed on the fact that the oak species (Quercus robur) is one of the most valuable species on Ukraine’s territory. Optimum growth conditions are found in the forest-steppe zone. Ukraine’s stands of oak underwent the most destruction in the 16th –19th centuries. The midtwentieth century witnessed a trend for a gradual increase in forest land areas with oak being the prevailing species. Thus, stands of oak amounted 1710,3 thousand hectars, as of January 1, 2002, which represents about 27 percent of forest land area within the boundaries of West forest-steppe and the Pre-Carpathian Zone. Stands of oak in mixture with other species occupy an area of over 451,3 thousand hectars, that is about 27 percent of all stands of oak in our country. The state enterprise “Sambir Lisnytstvo” (Sambir forest district) has investigated the dynamics of increase in the rate of growth for common oak in the old-growth stands. It was revealed that after thinning cuts in 2005, this species tends to gradually increase its rate of growth. The good seed year of 2007 did not effect the tendency toward accelerating the stands increment. So, there good reasons to believe that this tendency will be further persisting.